Analysis of geosynthetic reinforcement in pile-supported embankments. Part II: 3D cable-net model. Issue 2 (April 2010) - Halvordson, K.A.; Plaut, R.H.; Filz, G.M.
Abstract : ABSTRACT: In this second part of a three-part study, the geogrid reinforcement is modelled as a three-dimensional cable net. Square pile caps are considered. Again, symmetry is utilised, and numerical results are obtained by minimising the total energy. The cables are connected at nodes, which are represented as spherical joints with variable rotational stiffness. Nodal displacements are computed, and strains and stress resultants can then be calculated from them. The net stress reduction ratio is also found. The effects of variations in the following quantities are determined: the size of the pile caps; the stress on the geosynthetic over the soft soil between the piles; the stiffness of the soft soil; the spacing between geogrid nodes; the orthotropy of the geogrid; and the bending stiffness (modelled by rotational springs) at the nodes. In addition, the effect of rotation of the geogrid by 45° is analysed, in which each rib is parallel to one of the diagonals of the unit cell. Also, the case of two geogrid layers is treated. As for the plate model, large spikes in strain and stress occur near the corners of the pile caps, and three-dimensional effects are important.